Losartan Reverses Hippocampal Increase of Kynurenic Acid in Type 1 Diabetic Rats: A Novel Procognitive Aspect of Sartan Action - Iwona Chmiel-Perzyńska; Adam Perzyński; Bartosz Olajossy; Paulina Gil-Kulik; Janusz Kocki; Ewa M. Urbańska (Journal of Diabetes Research)
Patients with diabetes mellitus (DM) type 1 and 2 are at a higher risk of cognitive decline and dementia; however, the underlying pathology is poorly understood. Kynurenic acid (KYNA), endogenous kynurenine metabolite, displays pleiotropic effects, including a blockade of glutamatergic and cholinergic receptors. Apart from well-known glial origin, kynurenic acid is robustly synthesized in the endothelium and its serum levels correlate with homocysteine, a risk factor for cognitive decline. Studies in an experimental DM model suggest that a selective, hippocampal increase of the kynurenic acid level may be an important factor contributing to diabetes-related cognitive impairment. The aim of this study was to assess the effects of chronic, four-week administration of losartan, angiotensin receptor blocker (ARB), on the brain KYNA in diabetic rats. Chromatographic and rt-PCR techniques were used to measure the level of KYNA and the expression of genes encoding kynurenine aminotransferases, KYNA biosynthetic enzymes, in the hippocampi of rats with streptozotocin-induced DM, treated with losartan. The effect of losartan on KYNA synthesis de novo was also evaluated in vitro, in brain cortical slices. The hippocampal increase of KYNA content occurred in diabetic rats treated and nontreated with insulin. Losartan did not affect KYNA levels when administered per se to naïve or diabetic animals but normalized KYNA content in diabetic rats receiving concomitantly insulin. The expression of CCBL1 (kat 1), AADAT (kat 2), and KAT3 (kat 3) genes did not differ between analyzed groups. Low concentrations of losartan did not affect KYNA production in vitro. The neuroprotective effect of ARBs in diabetic individuals may be, at least partially, linked to modulation of KYNA metabolism. The ability of ARB to modulate synthesis of KYNA in diabetic brain does not seem to result from changed expression of genes encoding KATs. We propose possible involvement of angiotensin AT4 receptors in the observed action of losartan.